REGENERATION OF TAIL IN THE EEL MURAENESOX TALABONOIDES (BLEEKER) - George, M K (Indian Journal of Fisheries, 2011)
Regeneration of caudal fins among fishes of the Indian region has been reported (Menon 1951, Jones and Menon 1952, and Bensam 1965). In the eel, Muraenesox talabonoides studied here, regeneiiation beyond the base of caudal fin is common and hence, morphological and anatomical details and the proportion of length of tail to that of trunk are effected.